(untitled) (Research, Society and Development, 2019)
Solid Mechanics is a basic and fundamental discipline, of several courses of Engineering, since it studies the behavior of the bodies with the objective of determining the values of stress and strains when they are subject to different loads. In this context, several studies report difficulties of students and teachers in the teaching-learning of this discipline. This difficulty is common because this discipline covers studies of great scientists over several centuries, studies that are difficult to understand and interpret. The present article aims of presenting the Geometric Properties module of the BEAMS program (Exercises Bank Applied to Solid Mechanics). This program allows the development of fundamental concepts of Solid Mechanics, leading at student learning, with the detail of each calculation, not being a program essentially focused on results. The program has being developed using the software Scilab, and the module "Geometric Properties", already implemented, allows the calculation of the area, geometric center and moment of inertia of an asymmetrical cross section in an I-shape. visualize the influence of the dimensions of the cross section on the position of the center of gravity and on the values of the moment of inertia, facilitating to the student the learning of these concepts. Some potential results already achieved are the automation of the process; the updating of the calculations and texts according to each type of cross section and the resizing of the image according to the dimensions inserted.